KEWAJIBAN PT. TITIPAN KILAT PONTIANAK UNTUK MEMBAYAR IURAN HAK JAMINAN PEKERJA PADA BADAN PENYELENGGARA JAMINAN SOSIAL (BPJS) KETENAGAKERJAAN - NIM. A1011161034, MUHAMMAD FAJAR (Fakultas Hukum Universitas Tanjungpura, 2022)
AbstractThe company or employer has the right and responsibility to provide social security for workers, in accordance with law No. 13 of 2003 on employment and law No. 24 of 2011 on BPJS. In practice, there are still many companies that do not pay the BPJS employment contributions regularly and in an orderly manner, resulting in arrears which result in workers not being able to receive their rights in accordance with the BPJS program they are participated in.PT. Titipan Kilat Pontianak as an employer, you have an obligation in accordance with the provisions of the law to register your workers as participants, who then collect contributions from workers and deposit the BPJS employment contributions in accordance with the program they have participated in. PT. Titipan Kilat Pontianak has ever been in arrears in the payment of these contributions, which led to legal consequences for the arrears that occurred.In this case, workers will automatically not be able to claim social security rights in the form of old age insurance, work accident insurance, pension benefits, and death benefits which are the rights of workers and their heirs if the company does not pay the BPJS employment contributions. The company must first pay the entire contribution fee as borne by the BPJS for employment to given to workers who have a work accident and then after the company has paid all the arrears and fines, it can claim to the BPJS for manpower.Keywords : Social Security, Social Security Administering Agency Employment, Delayed Payment Of Contributions ABSTRAKPerusahaan atau pemberi kerja memilki hak dan tanggung jawab untuk memberikan Jaminan Sosial Tenaga Kerja kepada pekerjanya, sesuai dengan Undang